Tolerance to Zn toxicity in the halophyte Lepidium latifolium L. and the effect of salt on Zn tolerance and accumulation - Behzad NEZHADASAD-AGHBASH; Tayebeh RADJABIAN; Roghieh HAJIBOLAND (Acta Agriculturae Slovenica, 2023)
Halophytes exhibit a high cross-tolerance to multiple stresses that enable them to survive under harsh environmental conditions. We hypothesized that salt treatment in halophytes improves their tolerance against other stressors. To investigate the salt-mediated heavy metal tolerance in halophytes, Lepidium latifolium (Brassicaceae) was cultivated in the absence or presence of salt (100 mM NaCl) and excess Zn (200 μM ZnSO4), alone or in combination, for four weeks in the hydroponic medium. Salt treatment ameliorated the reduction of photosynthetic pigments in Zn-stressed plants and decreased Zn accumulation in the young leaves. The activity of peroxidase increased by both Zn toxicity and salt treatments; its maximum activity was achieved under the combination of both treatments associated with a significant reduction in malondialdehyde concentration. The activity of polyphenol oxidase increased by Zn stress alone or in combination with salt, accompanied by accumulation of free and cell wall-bound phenolics and enhanced lignin deposition in the leaves. Our results showed a mitigating effect of salt treatment in Zn-stressed plants through the activation of antioxidant defense and accumulation of phenolic compounds including flavonoids. Our results suggest L. latifolium as suitable species for revegetation and rehabilitation of saline soils contaminated with heavy metals.